Elevated Ca2+ at the triad junction underlies dysregulation of Ca2+ signaling in dysferlin-null skeletal muscle - Lukyanenko, Valeriy; Muriel, Joaquin; Garman, Daniel; Breydo, Leonid; Bloch, Robert J. (Frontiers in Physiology, 2022)
Dysferlin-null A/J myofibers generate abnormal Ca2+ transients that are slightly reduced in amplitude compared to controls. These are further reduced in amplitude by hypoosmotic shock and often appear as Ca2+ waves (Lukyanenko et al., J. Physiol., 2017). Ca2+ waves are typically associated with Ca2+-induced Ca2+ release, or CICR, which can be myopathic. We tested the ability of a permeable Ca2+ chelator, BAPTA-AM, to inhibit CICR in injured dysferlin-null fibers and found that 10-50 nM BAPTA-AM suppressed all Ca2+ waves. The same concentrations of BAPTA-AM increased the amplitude of the Ca2+ transient in A/J fibers to wild type levels and protected transients against the loss of amplitude after hypoosmotic shock, as also seen in wild type fibers. Incubation with 10 nM BAPTA-AM led to intracellular BAPTA concentrations of ~60 nM, as estimated with its fluorescent analog, Fluo-4AM. This should be sufficient to restore intracellular Ca2+ to levels seen in wild type muscle. Fluo-4AM was ~10-fold less effective than BAPTA-AM, however, consistent with its lower affinity for Ca2+. EGTA, which has an affinity for Ca2+ similar to BAPTA, but with much slower kinetics of binding, was even less potent when introduced as the -AM derivative. By contrast, a dysferlin variant with GCaMP6fu in place of its C2A domain accumulated at triad junctions, like wild type dysferlin, and suppressed all abnormal Ca2+ signaling. GCaMP6fu introduced as a Venus chimera did not accumulate at junctions and failed to suppress abnormal Ca2+ signaling. Our results suggest that leak of Ca2+ into the triad junctional cleft underlies dysregulation of Ca2+ signaling in dysferlin-null myofibers, and that dysferlin’s C2A domain suppresses abnormal Ca2+ signaling and protects muscle against injury by binding Ca2+ in the cleft.